Transaction Costs And Location On Customer Loyalty Of Brilink Agents In Bangko Semprina - Rika Malia; M. Irwansyah Hasibuan; Meisa Fitri Nasution (Citakonsultindo, 2026)
This study aims to analyze the effect of transaction costs and location on customer loyalty of BRILink Agent Dayu in Bangko Perfect . This research uses a quantitative descriptive approach with data collected through questionnaires distributed to 60 respondents selected via random sampling. The data were analyzed using multiple linear regression with SPSS version 26, including validity test, reliability test, coefficient of determination (R²), partial t-test, and simultaneous F-test. The results show that transaction costs have a positive and significant effect on customer loyalty (t-value 8.559 > t-table 2.000, sig. 0.000 < 0.05). Location also has a positive and significant effect on customer loyalty (t-value 2.548 > t-table 2.000, sig. 0.014 < 0.05). Simultaneously, both variables significantly affect customer loyalty (F-value 115.108 > F-table 3.159) with an R² value of 0.802. The findings of this study confirm that affordable and transparent transaction costs along with a strategic and accessible location are key factors in enhancing customer loyalty at BRILink Agent Dayu in Bangko Perfect .